Technical Variables in Lower Extremity Free Flap Reconstruction - Christensen, Joani M.; Ahn, Leah; Meulendijks, Mara Z.; Iskhakov, David; Wong, Frankie; Winograd, Jonathan; Valerio, Ian L.; Cetrulo, Curtis L., Jr.; Helliwell, Lydia A.; Eberlin, Kyle R. (Journal of Reconstructive Microsurgery, 2023)
Background Lower extremity free flap failure rates are higher than in other areas of the body. While prior studies assessed the effect of intraoperative technical variables, these generally investigated individual variables and did not examine relationships between the many individual technical decisions made during free tissue reconstruction. Our purpose was to investigate the effect of variation in intraoperative microsurgical techniques on flap outcomes in a diverse cohort of patients requiring lower extremity free flap coverage.Methods Consecutive patients undergoing free flap reconstruction of the lower extremity at two level 1 trauma centers from January 2002 to January 2020 were identified using Current Procedural Terminology codes, followed by a review of medical records. Information regarding demographics and comorbidities, indications, intraoperative technical details, and complications was collected. Outcomes of interest included an unplanned return to the operating room, arterial thrombosis, venous thrombosis, partial flap failure, and total flap failure. Bivariate analysis was performed.Results In total, 410 patients underwent 420 free tissue transfers. The median follow-up time was 17 months (interquartile ranges: 8.0–37). Total flap failure occurred in 4.9% (n = 20), partial flap failure in 5.9% (n = 24), and unplanned reoperation in 9.0% (n = 37), with arterial thrombosis in 3.2% (n = 13) and venous thrombosis in 5.4% (n = 22). Overall complications were significantly associated with recipient artery choice, with arteries other than PT and AT/DP having a higher rate (p = 0.033), and with arterial revisions (p = 0.010). Total flap failure was also associated with revision of the arterial anastomosis (p = 0.035), and partial flap failure was associated with recipient artery choice (p = 0.032).Conclusion Many interoperative options and techniques are available when performing microvascular lower extremity reconstruction that leads to equally high success rates. However, the use of arterial inflow outside of the posterior tibial and anterior tibial arteries leads to a higher overall complication rate and partial flap failure rate. Intraoperative revision of the arterial anastomosis portends poorly for ultimate flap survival.
Keywords: free flap; lower extremity; microsurgery; microvascular lower extremity; reconstruction; limb salvage